Pragmalinguistic Aspects of English Dialogic Speech - Sabiya Nuridinova Alahiddinovna (Researchparks Publishing, 2023)
The aim of the article is determined by the fact that the appeal to various social, psychological, personal, and individual characteristics of a person is of particular interest for research in the field of linguistics, psycholinguistics, sociolinguistics, and ethnolinguistics related to the human factor.